Application of inhibitor JAK1 and JAK2 ruxolitinib as pre- and posttransplant therapy in patients with myelofibrosis - M. V. Barabanshchikova; E. V. Morozova; Yu. Yu. Vlasova; V. V. Baykov; L. S. Zubarovskaya; B. V. Afanasyev (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Primary myelofibrosis (PMF) is а chronic BCRABL–negative myeloproliferative disorder with progressive clinical course. Allogeneic stem cell transplantation is the only treatment optionin patients with PMF with curative potential. Most of PMF patients have active disease phase at the moment of alloHSCT. The Januskinase inhibitor ruxolitinib is effective in decreasingof tumor mass before alloHSCT. Here we report our experience in administration of ruxolitinib as pre and posttransplant therapy of patients with PMF as well as patients with polycythemia vera and essential thrombocythaemia with transformation into myelofibrosis.